2022
DOI: 10.1002/anie.202200352
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Dual‐Base‐Enabled Nickel‐Catalyzed Aryl Amidations: Application in the Synthesis of 4‐Quinolones

Abstract: The CÀ N cross-coupling of (hetero)aryl (pseudo)halides with NH substrates employing nickel catalysts and organic amine bases represents an emergent strategy for the sustainable synthesis of (hetero)anilines. However, unlike protocols that rely on photoredox/electrochemical/reductant methods within Ni I/III cycles, the reaction steps that comprise a putative Ni 0/II CÀ N cross-coupling cycle for a thermally promoted catalyst system using organic amine base have not been elucidated. Here we disclose an efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 71 publications
2
18
0
Order By: Relevance
“…Recently, Stradiotto [4c] proposed a Ni 0/II pathway in nickel catalyzed amidation under thermal catalytic conditions, and suggested that the reductive elimination of a putative (L)‐Ni(II)(2‐Ac−Ph)(amido) species bearing a bisphosphine ligand is facile. Bahamonde and co‐workers [8b] proposed a Ni 0/I/II/III pathway in Ni‐photoredox mediated amidation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Stradiotto [4c] proposed a Ni 0/II pathway in nickel catalyzed amidation under thermal catalytic conditions, and suggested that the reductive elimination of a putative (L)‐Ni(II)(2‐Ac−Ph)(amido) species bearing a bisphosphine ligand is facile. Bahamonde and co‐workers [8b] proposed a Ni 0/I/II/III pathway in Ni‐photoredox mediated amidation.…”
Section: Resultsmentioning
confidence: 99%
“…When 6a was treated with a combination of 9-azajulolidine and sodium t -pentoxide, we observed the reductive elimination product N -phenyl- N -adamantyl amine in 26% yield (Figure ). , These results represent a proof of principle that reductive elimination can be induced using a suitable set of reagents.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, we opted to conduct an alternative screening campaign using the inexpensive and soluble organic amine base DBU, paired with the presumptive chloride scavenger NaTFA (so‐called ‘dual‐base’ system [18] ). While we have successfully applied this approach in nickel‐catalyzed C−N cross‐couplings of fluoroalkylamines and amides, [17i–k] as well as in challenging α‐arylation chemistry, [27] the application of dual‐base systems remains unexplored in the context of nickel‐catalyzed C−N cross‐couplings involving nucleophiles a – d with (hetero)aryl chlorides. As with K 2 CO 3 , the catalytic performance achieved when using DBU/NaTFA was found to be inferior to that observed with NaO t Bu (Figure 3), with≥70 % conversion to the target complex being limited to following cases: 3 a ( C1 , C4 , and C5 ), 3 d ( C2 – C5 ), 4 a ( C1 , C4 , and C6 ), and 4 d ( C3 – C5 ).…”
Section: Resultsmentioning
confidence: 99%